Pengaruh Sistem Informasi Pembelian Tunai Terhadap Pengendalian Internal Pembelian Barang: Studi pada salah satu Yayasan Pendidikan di Kota Bandung - Erick Erick; Indah Damayanti; Roro Endah Kumalasari; Annita Jannah (Acman: Accounting and Management Journal, 2022)
This article aims to determine the magnitude of the influence of cash purchase information systems on internal control of purchasing goods at one of the educational foundations in the city of Bandung. Respondents are employees directly related to the purchase of goods as many as 35 employees. The researcher uses the correlation coefficient analysis technique, simple regression, and the coefficient of determination to determine the magnitude of the influence of the cash purchase information system on the internal control of purchasing goods. The calculation results show a significant effect of cash purchase information systems on internal control of purchasing goods. Recommendations from the research suggest improving the control environment, controlling activities, understanding risks, informing and communicating well from each individual or organization, and carrying out effective monitoring. In addition, improving the management system on purchase documents and others to be sustainable properly, such as archiving proof of purchase in physical form or stored in computer-based information technology.